IMPLEMENTASI PENDIDIKAN AGAMA ISLAM PADA ANAK AUTIS DI SKH AL-KHAIRIYAH, CILEGON - Ade Irma; Wasehudin Wasehudin; Fitri Hilmiyati; Yahdinil Firdha Nadhirah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Islamic religious education is the basic thing as the first education for autistic students because basically autistic students are not students who are categorized as crazy or amnesiac students, so these autistic students are still burdened with sharia law or taklif (legal burden). So in this study the researcher tries to present how the objectives, curriculum, implementation, evaluation and obstacles and challenges in Islamic Religious Education learning for students with special needs autism at SKh Al-Khairiyah, Cilegon City. This study uses a field research method or field research using a descriptive qualitative method with a prospective case study (Propestive Case Study). The data sources we use are primary data and secondary data. The results of the study show that the results of the implementation of learning in the autism class in the delivery of Islamic Religious Education teaching, a teacher applies the Social Story method and also the drill method (repetitions). In addition to classroom learning, the habits of religious practices are also trained consistently. While the evaluation model is not only with test and non-test evaluation, the evaluation is also carried out by observing information from people around, both from teachers, homeroom teachers and information from students' guardians regarding children's daily behavior.